Secreted frizzled‐related protein 4 and its implication in obesity and type‐2 diabetes. Issue 11 (13th July 2019) - Bukhari, Shazia Anwer; Yasmin, Aysha; Zahoor, Muhammad Asif; Mustafa, Ghulam; Sarfraz, Iqra; Rasul, Azhar
Abstract: Secreted frizzled‐related protein 4 (SFRP4) is a member of secreted protein family with sequence similarity to frizzled receptors of wingless‐related integration site (Wnt) signaling pathways. These proteins control diverse functions from embryonic development to adults in many organisms including humans. Initially, SFRPs were recognized as antagonists of Wnt signaling and supposed to interact with Wnts. Further research demonstrated their interactions to frizzled receptors and a functional diversity was related to these proteins, Wnt signaling potentiation in addition to modulation. SFRP4 is the largest member of SFRP family and is implicated in many diseases including obesity, type 2 diabetes (T2D), and cancer. SFRP4 acts as a biomarker for T2D and was expressed several years before clinical diagnosis of disease. This review mainly focusses on the role of SFRP4 in obesity and how it can lead to β‐cell failure and ultimately to T2D. The role of SFRP4 in adipose tissues causing increased production of adipokines lead to the oxidative stress in pancreas that particularly have low amount of antioxidant enzymes in pancreatic β‐cells leading to failure in exocytosis of insulin containing granules causing T2D. Obesity‐induced inflammation is a principal factor in pathogenesis of insulin resistance as well as metabolic syndrome. Pro‐inflammatory cytokines have potential to cause insulin resistance in skeletal muscles, adipose tissue, and liver via inhibition of insulin signal transduction. Secretion of SFRP4 is mediated by interleukin 1‐β (IL1‐β). This review highlights the molecular mechanisms by which SFRP4 leads to T2D. Understanding of molecular mechanism and targeting SFRP4 could help to eradicate or reduce chances of developing T2D.